Base free transfer hydrogenation using a covalent triazine framework based catalyst. Issue 29 (26th May 2017) - Bavykina, A. V.; Mautscke, H.-H.; Makkee, M.; Kapteijn, F.; Gascon, J.; Llabrés i Xamena, F. X.
Abstract : Isomerisation of allylic alcohols to saturated ketones can be efficiently catalysed by a heterogeneous molecular system resulting from Ir III Cp* anchoring to a covalent triazine framework. Abstract : Isomerisation of allylic alcohols to saturated ketones can be efficiently catalysed by a heterogeneous molecular system resulting from Ir III Cp* anchoring to a covalent triazine framework. The obtained catalysts are active, selective, and fully recyclable.